2019
DOI: 10.12659/msm.912876
|View full text |Cite
|
Sign up to set email alerts
|

Long Non-Coding RNA AWPPH Promotes Postoperative Distant Recurrence in Resected Non-Small Cell Lung Cancer by Upregulating Transforming Growth Factor beta 1 (TGF-β1)

Abstract: Background Postoperative recurrence of cancers is responsible for a large portion of deaths in cancer patients. Our study investigated the involvement of lncRNA AWPPH in recurrence of resected non-small cell lung cancer (NSCLC). Material/Methods A total of 128 patients were followed up for 3 years. Blood was extracted from each patient on the day of discharge, the day of the diagnosis of recurrence, or at the end of follow-up. Blood from 30 healthy controls was used as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…Many of these lncRNAs are regulated by TGF-β. [11][12][13][14][15] LncRNAs play essential roles in the migration, invasion and EMT and are discovered to act as miRNA sponges to participate in cancer progression. [16][17][18] Our previous study has shown that six lncRNAs, including LINC02323, are associated with metastasis and prognosis of LUAD.…”
Section: Introductionmentioning
confidence: 99%
“…Many of these lncRNAs are regulated by TGF-β. [11][12][13][14][15] LncRNAs play essential roles in the migration, invasion and EMT and are discovered to act as miRNA sponges to participate in cancer progression. [16][17][18] Our previous study has shown that six lncRNAs, including LINC02323, are associated with metastasis and prognosis of LUAD.…”
Section: Introductionmentioning
confidence: 99%
“…The positive roles of miRNAs and lncRNAs can be concluded as follows: miR-93 [59], miR-128-3p [61], miR-9 [62], miR-134, miR-487b [65], miR-330-3p [67], miR-1246 [68], miR-23a [74], HCP5 [107], NORAD [18], XIST [19,20], linc00673 [109], MEG3 [110], MEG8 [111], and ATB [113] can enhance TGF-β signaling-induced EMT. MiR-9 [63], miR-9-5p [71], ATB [112], TBILA [115] lnc-MMP2-2 [116], and AWPPH [117] can accelerate TGF-β signaling-mediated lung cancer cell migration and invasion. Lnc-MMP2-2 can also increase vascular permeability [116].…”
Section: Discussionmentioning
confidence: 99%
“…lnc-MMP2-2→E-cadherin↓, N-cadherin↑, vimentin↑→invasion↑, migration↑ [116] lnc-MMP2-2→occludin↓, Zo-1↓→vascular permeability↑ lnc-MMP2-2→MMP2↑→metastasis↑ lncRNA AWPPH NCI-H1993, NCI-H2170 AWPPH→TGF-β1↑→invasion↑, migration↑ [117] lncRNA CASC11 SHP-77, DMS79 CASC11→TGF-β1↑→stemness↑ [118] Abbreviations: nc-RNA, non-coding RNA; miR, microRNA; NEDD4L, Neural precursor cell expressed developmentally downregulated gene 4-like; TGF-β, transforming growth factor-β; EMT, epithelial-mesenchymal transition; SMURF2, Smad ubiquitin regulatory factor 2; cPP1, catalytic subunit of protein phosphatase 1; MAGI2, membrane-associated guanylate kinase, WW and PDZ domain-containing protein 2; SOX7, SRY-Box 7; TGFBR2, TGF-β receptor 2; lncRNA, long non-coding RNA; HCP5, histocompatibility leukocyte antigen complex P5; XIST, X inactivate-specific transcript; ZEB2, Zinc finger E-box-binding homeobox 2; lncRNA-ATB, lncRNA activated by TGF-β; AKT, protein kinase B; JAK, Janus-activated kinase; STAT3, signal transducer and activator of transcription-3; TBILA, TGF-β-induced lncRNA; HGAL, human germinal center-associated lymphoma; JAB1, c-Jun activation domain-binding protein 1; Zo-1, zonula occludens-1; MMP2, matrix metalloprotease 2. [106] lncRNA HAND2-AS1 H1581, H1993 HAND2-AS1→TGF-β1/Smad2/3 signal↓→invasion↓, migration↓, stemness↓ [119] lncRNA linc01186 A549 linc01186→EMT↓→invasion↓, migration↓ [120] lncRNA LINP1 A549 LINP1→E-cadherin↑, vimentin↓, Snail↓→EMT↓ [121] lncRNA ANCR NCI-H23, NCI-H522 ANCR→TGF-β1↓→invasion↓, migration↓ [122] lncRNA NKILA A549, H226 NKILA→NF-κB↓→Snail↓→EMT↓→invasion↓, migration↓ [123] Abbreviations: nc-RNA, non-coding RNA; miR, microRNA; EMT, epithelial-mesenchymal transition; TGF-β, transforming growth factor-β; SULF2, Sulfatase 2; ZEB1, Zinc finger E-box-binding homeobox 1; MTDH, metadherin; FOXM1, forkhead Box M1; FOXQ1, forkhead box Q1; Sp1, specificity protein 1; SOX4, sex-determining region Y-box 4; TGFBR1, TGF-β receptor 1; CCNE2, cyclin E2; AKT, protein kinase B; CSCs, cancer stem cells; lncRNA, long non-coding RNA; LINP1, lncRNA in nonhomologous end joining (NHEJ) pathway 1; NF-κB, nuclear factor-kappa B; NKILA, NF-κB Interacting LncRNA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many recent studies have demonstrated the abnormal expression of various long noncoding RNAs (lncRNAs) in non-small cell lung cancer (NSCLC) (31)(32)(33). These dysregulated lncRNAs act as important regulators of the pathogenesis of NSCLC and have crucial effects on NSCLC tumorigenesis, progression, and metastasis (34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%